2019
DOI: 10.1097/md.0000000000017956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kinesio taping of the knee on proprioception, balance, and functional performance in patients with anterior cruciate ligament rupture

Abstract: To investigate whether Kinesio tape (KT) application improves proprioception, balance, and functional performance in patients with anterior cruciate ligament rupture (ACLr). This retrospective analysis included 48 male patients with surgically-untreated ACLr who attended the Sports Medicine and Rehabilitation Center, Qingdao Municipal Hospital, China between June 2017 and June 2018. KT was applied to induce a detoning effect on the quadriceps muscle and toning effect on the ischiocrural muscles. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
1
24
0
3
Order By: Relevance
“…It places constant shear to the skin because of its adherence properties that mimic those of the skin, and it can be used for 3 to 4 days without removal [6]. One of the proposed mechanisms of Kinesio™ tape is to enhance proprioceptive sensibility after application, as it supports weak muscles, improves muscle functioning, decreases pain, repositions subluxated joints, and facilitates blood and lymph circulation [6][7][8]. These effects allow affected fascia and muscle to return to normal functioning by decreasing abnormal muscle tension and improving joint function [9].…”
Section: Introductionmentioning
confidence: 99%
“…It places constant shear to the skin because of its adherence properties that mimic those of the skin, and it can be used for 3 to 4 days without removal [6]. One of the proposed mechanisms of Kinesio™ tape is to enhance proprioceptive sensibility after application, as it supports weak muscles, improves muscle functioning, decreases pain, repositions subluxated joints, and facilitates blood and lymph circulation [6][7][8]. These effects allow affected fascia and muscle to return to normal functioning by decreasing abnormal muscle tension and improving joint function [9].…”
Section: Introductionmentioning
confidence: 99%
“…This result is supported by the results of previous studies that explored knee joint position sense in healthy subject after taping for 24 h ( Torres et al, 2016 ). However, Liu et al (2019) established that KT can improve the knee proprioception of patients with anterior cruciate ligament (ACL) injury. Cho et al (2015) found that KT potentially improves positive knee joint position sense in patients with knee osteoarthritis after 1 h. Callaghan et al (2008) showed that the poor proprioception of patients with patellofemoral pain syndrome can be improved after taping.…”
Section: Discussionmentioning
confidence: 99%
“…Kinesiology taping (KT), an elastic, water-resistant, and air permeable tape, was developed by Kenzo Kase in the 1970s, the tape can stretch to 120–140% of its original length and can recoil after application ( Kase et al, 2003 ). On the basis of its special features, the compressive and shear force applied by the tape on the skin activates cutaneous mechanoreceptors related to joint position, movement, and force ( Kase et al, 2003 ), conveying more information from the knee joint to the central nervous system for integration and, therefore, resulting in enhanced proprioception ( Riemann and Lephart, 2002 ; Liu et al, 2019 ). Previous studies verified that the recoiling force direction of the tape is the same as that of a muscle contraction, is potentially transmitted to the fascia and facilitates a target muscle’s production of high force ( Kuo and Huang, 2013 ; Yam M. L. et al, 2019 ; Ye et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I believed that KT elicits the proprioception sense through increased stimulation of cutaneous mechanoreceptors. 26 Schultz et al 27 published the first detailed description of mechanoreceptors in human and suggested that they may have a proprioceptive function. Adachi et al 28 also reported that mechanoreceptors contribute to the joint position sense.…”
Section: Discussionmentioning
confidence: 99%